Response of Broiler Chickens to Palm Kernel Cake and Maize Offal Mixed in Different Ratios - Onuh, S.O.; Ortserga, D.D.; Okoh, J.J. (Pakistan Journal of Nutrition, 2010)
A total of one hundred and twenty (120) unsexed broiler chickens of 5 days of age averaging 59.50±1.00 grams were randomly allocated into 4 dietary treatments designated I, II, III and IV to evaluate the effect of different ratios of palm kernel cake and maize offal mixed in the ratios of 1:1, 3:1 and 4:1 for treatments II, III and IV respectively and these were compared with the control diet at the starter and finishing phases. Each treatment was replicated 2 times. The results at the starter phase show that there were no significant differences (p>0.05) in feed intake and efficiency of feed utilization among birds fed all diets. There were also no significant differences (p>0.05) in feed cost per unit weight gain among birds fed the control diet and those fed the diets which contained 1:1 and 4:1 ratio of palm kernel cake and maize pap offal. However, the results at the finishing phase show that the diet which contained 3:1 ratio of palm kernel cake and maize pap offal significantly increased (p